The new institution of the "Pubic independent conciliator" in the North- West and South-West regions: reflection on the effectiveness and relevance of an innovation in the reform of the law of decentralised territorial authorities in Cameroon (African Journal of Law and Politics, 2023)
The adoption of a public independent conciliator, an independent authority, in the North-West and South-West regions of Cameroon stems from several factors. In particular, there is a desire to ensure the protection of citizens against the communal and regional administration, to promote the participation of an independent body in guaranteeing their rights, and to humanise relations between the decentralised administration and citizens. In order to meet this cardinal objective, the public authorities have granted the public independent conciliator a status and a legal regime that reflect an organised efficiency. However, the application of the chosen system ends with a relative efficiency. This is the result of the mismatch between the relatively limited means available and the importance of the missions.